Impact Analysis of Infrastructural Renewal on Nigerian Economy (Lapai Journal of Economics, 2019)
This paper investigates the impact analysis of infrastructural renewal on Nigerian economy. The data used is time series between 1981 to 2017 for government spending on road, communication, education and private capital. The sources of the data are from National Bureau of Statistics, Central Bank of Nigeria and World Development Index. In order to avoid spurious results, Augmented Dickey Fuller’s stationarity test and Johansen’s co-integration test was conducted while Vector Error Correction Model (VECM) was employed as methodology to analyse the results. Findings show that government spending on infrastructure has long-run relationship with Nigerian economy. Government expenditure on road and communication has positive and significant impact on Nigerian economy. Government expenditure and private investment has negative but significant impact on Nigerian economy. The study recommends that government should improve expenditure on road and education in order to boast economy and bring the economy to path of progress and prosperity. Since the government alone cannot provide all infrastructures for the citizens, it should partner with private sector using Public Private Partnership in the provision of infrastructure amenities in order to increase economic growth in Nigeria.